Co-Formations : des spatialités de résistance décoloniales chez les lesbiennes « of color » en France - Paola Bacchetta (Genre, Sexualité et Société)
This article argues that lesbians “of color” in France are creating new decolonial subjectivities and resistant practices, yet these remain unintelligible in the dominant grid of intelligibility because the grid can not account for the inseparability of gender, sexuality, “race”-racism, class, slavery and postslavery, colonialism and postcoloniality.  Part one reviews contributions and limitations of current feminist and queer theorizing, and proposes the concepts of co-formations and co-productions to keep these invisibilized inseparabilities under consideration. Part two analyzes four modes of resistance (psychic, transgressive, transformative and directly oppositional) via these two concepts, underscoring that which otherwise falls in the shadows. The article concludes that lesbians “of color” are always already working with inseparabilities even when not articulated as such, and that the concept of co-formations can provide a means to keep these inseparabilities visible.